Nostalgia as Cultural Currency: How Java's Millennials Invest in Heritage Brands for Identity and Continuity - Riu, Isma Azis (Abadi Institute, 2025)
This narrative inquiry explores the resurgence of local heritage brands among urban millennial consumers in Java, Indonesia, examining nostalgia as a primary emotional driver of purchasing behavior. Through in-depth interviews with 30 participants across five major Javanese cities (Jakarta, Bandung, Semarang, Yogyakarta, Surabaya), supplemented by sensory elicitation techniques, the study reveals how heritage consumption functions as temporal integration weaving personal nostalgia (e.g., childhood memories evoked by jamu’s bitterness or batik’s texture) with constructed cultural heritage. Findings identify a nuanced authenticity paradox: participants demanded visible craftsmanship as proof of intergenerational integrity while strategically embracing modernization that preserves cultural essence. Heritage brands emerged as tools for hybrid identity work, enabling millennials to reclaim Javanese identity within globalized selves through embodied rituals (e.g., lulur skincare as cultural homage). The emotional landscape featured reflective nostalgia, bittersweet resonance, balancing comfort with awareness of cultural transformation, and transforming consumption into agentive cultural resilience. Ultimately, purchasing decisions represent ethical stewardship, sustaining intangible heritage through market mechanisms (